Polysaccharide-based thermoplastic composite fiber and preparation method thereof

By introducing large volumes of benzene ring groups on the polysaccharide molecular chain, polysaccharide-based thermoplastic materials are prepared, and polysaccharide/PBAT composite fibers are prepared through melt blending and melt spinning technology, the problem of poor mechanical properties of existing PBAT composite materials is solved, and the high mechanical properties and good compatibility of the materials are achieved.

CN119777031APending Publication Date: 2025-04-08INST OF CHEM CHINESE ACAD OF SCI +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411973004.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The mechanical properties of existing PBAT composite materials are poor, and the graft modification methods currently used are cumbersome, making it difficult to effectively improve the interfacial compatibility and mechanical properties of the materials.

Method used

By introducing large volumes of benzene ring groups on the polysaccharide molecular chain, polysaccharide-based thermoplastic materials with high thermal motion capabilities are prepared, and polysaccharide/PBAT composite fibers are prepared through melt blending and melt spinning technology to improve the compatibility and mechanical properties of the material.

Benefits of technology

It achieves good compatibility between polysaccharides and PBAT, improves the mechanical properties of composite materials, especially tensile strength and elongation at break, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119777031A_ABST
    Figure CN119777031A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of bio-based thermoplastic polymer materials, and particularly relates to a polysaccharide-based thermoplastic composite fiber and a preparation method thereof. The method comprises the following steps: S1, dissolving polysaccharide in a polysaccharide solvent by adopting a homogeneous method, and adding a reaction reagent A to realize molecular-level reaction, so as to obtain a polysaccharide-based thermoplastic material; s2, performing melt blending on the polysaccharide-based thermoplastic material and bio-based plastic, and then adding the mixture into melt spinning equipment for melt spinning to obtain the polysaccharide-based thermoplastic composite fiber. The polysaccharide-based thermoplastic material in the prepared polysaccharide-based thermoplastic composite fiber has good compatibility with PBAT, and the obtained composite material has good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of bio-based thermoplastic polymer materials, and in particular relates to a polysaccharide-based thermoplastic composite fiber and a preparation method thereof. Background Art

[0002] Natural polysaccharides, such as cellulose, starch and chitosan, have excellent biocompatibility and degradability. Natural polysaccharides have periodically distributed hydroxyl groups, which are modifiable. By chemically modifying the hydroxyl groups and introducing functional groups, polysaccharide derivatives can be obtained, which can give the polysaccharides more functionality, such as solubility, thermoplasticity, antibacterial and UV resistance. In addition, the introduction of functional groups can also increase the interfacial compatibility between polysaccharide derivatives and other materials, providing favorable conditions for the preparation of composite materials.

[0003] PBAT, a thermoplastic biodegradable plastic with good ductility and elongation at break, is a popular bio-based material on the market. There are also many reports on the use of PBAT to toughen cellulose materials, but the mechanical properties of the resulting composites are poor. In order to improve the interfacial compatibility between PBAT composites, methods such as compatibilizers (CN113248798A, CN113337013A) or grafting modifications (CN112552655A, CN114854180A) have been studied. Among them, grafting modification is the most promising, but the grafting methods currently used are relatively cumbersome. Summary of the invention

[0004] In order to improve the deficiencies of the prior art, the present invention provides a polysaccharide-based thermoplastic composite fiber and a preparation method thereof. The polysaccharide-based thermoplastic material in the polysaccharide-based thermoplastic composite fiber prepared by the present invention has good compatibility with PBAT, and the obtained composite material has good mechanical properties.

[0005] In a first aspect, the present invention provides a method for preparing a polysaccharide-based thermoplastic composite fiber, comprising the following steps:

[0006] S1. Using a homogeneous method, dissolving a polysaccharide in a polysaccharide solvent, adding a reaction reagent A to achieve a molecular-level reaction, and obtaining a polysaccharide-based thermoplastic material;

[0007] S2. The polysaccharide-based thermoplastic material and the bio-based plastic are melt-blended and then added into a melt-spinning device for melt spinning to obtain a polysaccharide-based thermoplastic composite fiber.

[0008] According to an embodiment of the present invention, S1 includes the following steps: dissolving a polysaccharide in a polysaccharide solvent to form a polysaccharide solution, adding a reaction reagent A to react, wherein the reaction reagent A contains a large-volume benzene ring group, and the large-volume benzene ring group is used to replace the hydroxyl group on the polysaccharide to obtain a polysaccharide-based thermoplastic material with high thermal mobility.

[0009] According to an embodiment of the present invention, the polysaccharide is selected from one or more of chitosan, starch, cellulose, xylan or pentosan, preferably at least one of starch, cellulose and xylan.

[0010] According to an embodiment of the present invention, the polysaccharide solvent is an ionic liquid, and the ionic liquid is selected from one or more of 1-ethyl-3-methylimidazolium chloride ionic liquid, 1-ethyl-3-methylimidazolium bromide ionic liquid, 1-allyl-3-methylimidazolium chloride ionic liquid, 1-allyl-3-methylimidazolium bromide ionic liquid, 1-butyl-3-methylimidazolium chloride ionic liquid, 1-butyl-3-methylimidazolium bromide ionic liquid, 1-ethyl-3-methylimidazolium acetate ionic liquid, 1-allyl-3-methylimidazolium acetate ionic liquid, 1-butyl-3-methylimidazolium acetate ionic liquid, 1-ethyl-3-methylimidazolium diethyl phosphate ionic liquid, N-methylpicolinate ionic liquid, 1-ethyl-3-methylimidazolium formate ionic liquid and 1-butyl-3-methylimidazolium formate ionic liquid.

[0011] According to an embodiment of the present invention, the polysaccharide solvent is selected from one or more of 1-allyl-3-methylimidazolium chloride ionic liquid, 1-butyl-3-methylimidazolium chloride ionic liquid, 1-ethyl-3-methylimidazolium acetate ionic liquid, and 1-butyl-3-methylimidazolium acetate ionic liquid.

[0012] According to an embodiment of the present invention, the concentration of the polysaccharide in the polysaccharide solution is 1-10wt%, preferably the concentration of the polysaccharide is 2-8wt%, exemplified by 2wt%, 3wt%, 5wt%, 7wt%, 8wt%.

[0013] According to an embodiment of the present invention, the temperature at which the polysaccharide is dissolved in the ionic liquid is 80-100°C, illustratively 80°C, 90°C or 100°C.

[0014] According to an embodiment of the present invention, the polysaccharide is dissolved in the ionic liquid for 1-3 hours, exemplarily 1 hour, 1.5 hours, 2 hours or 2.5 hours.

[0015] According to an embodiment of the present invention, the reaction reagent A is selected from at least one of cinnamoyl chloride, 3-phenylpropionyl chloride, 3-phenylpropionic acid, cinnamic acid, 2-trifluoromethylbenzoyl chloride, 2-trifluoromethylbenzoic acid, 2-methylbenzoyl chloride, 2-methylbenzoic acid, 2-oxytrifluoromethylbenzoyl chloride, phenylacetyl chloride, phenylacetic acid, 2-phenylpropionyl chloride, 2-phenylpropionic acid, 2-phenylbutyryl chloride, and 2-phenylbutyric acid, and is preferably one or more of cinnamoyl chloride, 3-phenylpropionyl chloride, 2-trifluoromethylbenzoyl chloride, and 3-phenylpropionic acid.

[0016] According to an embodiment of the present invention, the reaction temperature of the polysaccharide solution and the reaction reagent A is 40-60°C, preferably the reaction temperature is 45°C-60°C, for example 45°C, 50°C or 60°C.

[0017] According to an embodiment of the present invention, the reaction time of the polysaccharide solution and the reaction reagent A is 0.5-3 h, preferably the reaction time is 1-2 h, for example, 0.5 h, 1 h, 1.5 h or 2 h.

[0018] According to an embodiment of the present invention, after the polysaccharide solution reacts with the reaction reagent A, the following steps are further included: settling, washing, filtering and drying the reacted solution to obtain a polysaccharide-based thermoplastic material.

[0019] According to an embodiment of the present invention, the sedimentation agent selected for sedimentation is one or more of methanol, ethanol, isopropanol, water, and an alcohol / water mixture, preferably ethanol, methanol or an ethanol / water (V:V=5:5) mixed solution.

[0020] According to an embodiment of the present invention, the melt blending in step S2 is prepared by a twin-screw or internal mixer.

[0021] According to an embodiment of the present invention, the bio-based plastic is selected from one or more of PLA, PCL, PHA, PBS and PBAT, preferably PBAT.

[0022] According to an embodiment of the present invention, the thermal flow temperature of the PBAT is ≤120°C, for example, the thermal flow temperature of the PBAT is 112°C, 115°C, 118°C and 120°C.

[0023] According to an embodiment of the present invention, the molecular weight of the PBAT is 4w-8w, for example, 4.5w, 5.0w, 6.0w and 7.5w.

[0024] According to an embodiment of the present invention, the maximum thermal decomposition temperature of the PBAT is ≥370°C, such as 375°C, 377°C and 380°C.

[0025] According to an embodiment of the present invention, the bio-based plastic is PBAT, which forms a polysaccharide / PBAT composite material composition with a polysaccharide-based thermoplastic material. In the polysaccharide / PBAT composite material composition, the mass fraction of PBAT is 5-95wt%, for example, 10wt%, 30wt%, 50wt%, 70wt%, 70wt%, 80wt%, 85wt% and 90wt%.

[0026] According to an embodiment of the present invention, the melting comprises the following steps: premixing the dried polysaccharide-based thermoplastic material powder and the PBAT pellets in a high-speed mixer for 5-10 minutes; then, adding them to a preheated twin-screw or internal mixer for melt blending; finally, obtaining a polysaccharide / PBAT blend.

[0027] According to an embodiment of the present invention, before step S2, the following step is also included: blending the polysaccharide-based thermoplastic material / PBAT and drying them, for example, drying them in an oven at 60° C. for 2-3 hours.

[0028] According to an embodiment of the present invention, the temperature for melt blending the polysaccharide-based thermoplastic material and the bio-based plastic in step S2 is 80-120°C, for example, 110°C, 115°C and 120°C.

[0029] According to an embodiment of the present invention, the melt blending of the polysaccharide-based thermoplastic material and the bio-based plastic in step S2 includes the following steps: firstly drying the polysaccharide-based thermoplastic material and the bio-based plastic, mixing them evenly, and then melt mixing the mixture to obtain a polysaccharide-based thermoplastic material / bio-based plastic blend.

[0030] According to an embodiment of the present invention, the melt spinning in step S2 includes the following steps: adding the melt-blended polysaccharide-based thermoplastic material / bio-based plastic into a preheated barrel, and performing melt spinning after preheating for 3-5 minutes, the melt spinning temperature is 110-140°C, the melt spinning drawing speed is 10-100m / min, and the diameter of the melt-spun composite fiber is 50-100μm.

[0031] According to an embodiment of the present invention, in the polysaccharide-based thermoplastic material prepared in step S1, the polysaccharide-based thermoplastic material has a polysaccharide main chain, and the hydroxyl groups on the polysaccharide main chain are partially or completely replaced by bulky benzene ring groups.

[0032] According to an embodiment of the present invention, the glass transition temperature of the polysaccharide-based thermoplastic material is ≤100°C, preferably the glass transition temperature of the polysaccharide-based thermoplastic material is ≤95°C, preferably 95°C, 90°C, 85°C and 70°C;

[0033] According to an embodiment of the present invention, the heat flow temperature of the polysaccharide-based thermoplastic material is ≤120°C, preferably the heat flow temperature of the polysaccharide-based thermoplastic material is ≤115°C, exemplarily 113°C, 110°C, 100°C and 70°C.

[0034] In a second aspect, the present invention also provides a composite material composition, comprising a polysaccharide-based thermoplastic material and a bio-based plastic.

[0035] The polysaccharide-based thermoplastic material and the bio-based plastic have the definitions given above.

[0036] In a third aspect, the present invention further provides a polysaccharide-based thermoplastic composite fiber prepared by the above method, wherein the composite fiber has a tensile strength of 40-65 MPa and an elongation at break of 20-400%.

[0037] Beneficial Effects

[0038] 1) The present invention prepares a polysaccharide-based thermoplastic material with a similar structure to PBAT by introducing a bulky benzene ring group into the polysaccharide molecular chain that can simultaneously improve the interfacial compatibility between polysaccharide and PBAT and effectively promote the thermal movement ability of the polysaccharide, and then prepares a polysaccharide / PBAT composite material by melt blending, and then prepares a polysaccharide / PBAT melt-spun composite fiber by a melt spinning device.

[0039] 2) The polysaccharide / PBAT melt-spun composite fiber obtained by the preparation method of the present invention has good mechanical strength and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the NMR spectrum of the cellulose-based thermoplastic product prepared in Example 1.

[0041] Figure 2 This is the DSC graph of the cellulose-based thermoplastic product prepared in Example 1.

[0042] Figure 3 This is a thermal flow diagram of the cellulose-based thermoplastic product prepared in Example 1.

[0043] Figure 4 This is the NMR spectrum of the starch-based thermoplastic product prepared in Example 2.

[0044] Figure 5 This is the DSC graph of the starch-based thermoplastic product prepared in Example 2.

[0045] Figure 6 This is the thermal flow diagram of the starch-based thermoplastic product prepared in Example 2.

[0046] Figure 7 This is the NMR spectrum of the cellulose-based thermoplastic product prepared in Example 3.

[0047] Figure 8 This is the DSC graph of the cellulose-based thermoplastic product prepared in Example 3. DETAILED DESCRIPTION

[0048] The following will further describe the polysaccharide-based thermoplastic composite fiber of the present invention and its preparation method and application in combination with specific examples. It should be understood that the following examples are only for illustrative purposes to illustrate and explain the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope of protection of the present invention.

[0049] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0050] In the following examples, PBAT was derived from Lanshan Tunhe.

[0051] Example 1

[0052] (1) Preparation of cellulose-based thermoplastic materials

[0053] 10 g of dry cotton pulp with a degree of polymerization of about 560 was weighed and added to 190 g of ionic liquid solvent 1-allyl-3-methylimidazolium chloride (AmimCl), and dissolved with stirring at 80° C. for 2 h to obtain a cellulose / AmimCl solution with a mass fraction of 5 w%.

[0054] 22.92g(n AGU :n 酰氯 =1:2.5) of the reaction reagent A (3-phenylpropionyl chloride) was added to the cellulose / AmimCl solution (thermoplastic group is ) and stirred at 60°C for 2.0 hours. After the reaction, the reactant solution was precipitated in ethanol, and the crude product was washed three times with ethanol solution, filtered, and dried to obtain a cellulose-based thermoplastic product (CPp, the product is ).

[0055] The product was subjected to NMR test, and the test results were as follows: Figure 1 As shown, it is explained that a cellulose product substituted with phenylpropionate is obtained. In addition, the thermal properties of the cellulose-based thermoplastic product are characterized, and the DSC (differential scanning calorimeter) test results are shown in Figure 2 , indicating that the glass transition temperature of the obtained cellulose-based thermoplastic product is 92°C, which has good thermoplasticity.

[0056] Furthermore, the melt flow process of the cellulose-based thermoplastic material prepared in this example was observed on an Olympus BX5.1 optical microscope equipped with a Linkam THMS 600 hot stage. The specific observation steps were as follows: a small amount of sample was placed between two cover glasses and placed on the hot stage. The temperature was raised from 40°C to 240°C at a rate of 10°C / min. Microscope photos were taken every 10°C. The temperature at which the cellulose-based thermoplastic material was completely transparent and flowing was recorded as the melt flow temperature (Tf). The melt flow process was shown in FIG. Figure 3 As can be seen from the figure, the melt flow temperature of the cellulose-based thermoplastic material prepared in this embodiment is 100°C.

[0057] (2) Preparation of CPp / PBAT melt-spun composite fibers

[0058] Preparation of CPp / PBAT blend (CPp content of 20 wt%): 5 g of the dried CPp obtained in Example 1 and 20 g of PBAT (in this example, the heat flow temperature of PBAT is 113° C., the molecular weight is 4.5w, and the maximum pyrolysis temperature is 378° C.) were mixed in a mixer for 3 min to obtain a CPp / PBAT mixture, and then the CPp / PBAT mixture was melt-mixed in an internal mixer at 120° C. for 5 min to obtain a CPp / PBAT blend with a CPp content of 20 wt%.

[0059] The obtained blend is melt-spun on a melt spinning device, and the specific steps are as follows:

[0060] 20 g of the above CPp / PBAT blend was melt-spun on a spinning device at a spinning temperature of 125° C. and a winding speed of 20 m / min. The resulting CPp / PBAT melt-spun composite fiber had a diameter of 80 μm, a tensile strength of 52.5 MPa, and an elongation at break of 352%.

[0061] Example 2

[0062] (1) Preparation of cellulose-based thermoplastic materials

[0063] 10 g of dry corn starch was weighed and added to 190 g of 1-butyl-3-methylimidazolium acetate ionic liquid (BmimAc) solvent, and dissolved by stirring at 100° C. for 2.0 h to obtain a starch / BmimAc solution with a mass fraction of 5%.

[0064] 18.44g(n AGU :n 酰氯 =1:2.0) of the reaction reagent M (2-trifluoromethylbenzoyl chloride) was added to the starch / BmimAc solution (thermoplastic group is ) and stirred at 60°C for 2.5 hours. After the reaction, the reaction solution was precipitated in ethanol, and the crude product was washed three times with ethanol solution, filtered, and dried to obtain a thermoplastic starch product (AoOTFMB, the product is ).

[0065] The thermoplastic starch product was subjected to NMR testing, and the test results were as follows: Figure 4 As shown, it is shown that the starch product substituted with 2-trifluoromethyl benzoate is obtained. In addition, the thermal properties of the thermoplastic starch product substituted with 2-trifluoromethyl benzoate are characterized, and the DSC test results are shown in Figure 5 , indicating that the glass transition temperature of the obtained thermoplastic starch product is 70°C, and it has good thermoplasticity.

[0066] The melt fluidity of the starch product was tested using the same equipment and steps as in Example 1. At 110°C, it was observed that the 2-trifluoromethylbenzoate substituted starch product was completely melted. Figure 6 .

[0067] (2) Preparation of AoOTFMB / PBAT melt-spun composite fibers

[0068] Preparation of AoOTFMB / PBAT blend (AoOTFMB content is 16 wt%): 5 g of dried AoOTFMB and 26.25 g of PBAT (in this embodiment, the thermal flow temperature of PBAT is 110° C., the molecular weight is 6.5w, and the maximum pyrolysis temperature is 380° C.) are mixed in a mixer for 3 min to obtain an AoOTFMB / PBAT mixture, and then the AoOTFMB / PBAT mixture is melt-mixed on a 110° C. internal mixer for 6 min to obtain an AoOTFMB / PBAT blend with an AoOTFMB content of 16 wt%.

[0069] The obtained blend is melt-spun on a melt spinning device, and the specific steps are as follows:

[0070] 20 g of the above-mentioned AoOTFMB / PBAT blend was melt-spun on a homemade spinning device at a spinning temperature of 115° C. and a winding speed of 30 m / min to obtain AoOTFMB / PBAT melt-spun composite fibers. After testing, the diameter of the AoOTFMB / PBAT melt-spun composite fibers obtained in this embodiment was 78 μm, the tensile strength was 49.5 MPa, and the elongation at break was 369%.

[0071] Example 3

[0072] (1) Preparation of cellulose-based thermoplastic materials

[0073] 10 g of microcrystalline cellulose with a degree of polymerization of about 220 was weighed and added to 190 g of ionic liquid solvent 1-allyl-3-methylimidazolium chloride (AmimCl), and dissolved by stirring at 80° C. for 1.5 h to obtain a microcrystalline cellulose / AmimCl solution with a mass fraction of 5 wt %.

[0074] 25.73g(n AGU :n 酰氯 =1:3.0) was added to the microcrystalline cellulose / AmimCl solution (thermoplastic group is ) and stirred at 60°C for 2.0 hours. After the reaction, the reactant solution was precipitated in methanol, and the crude product was washed three times with methanol, filtered, and dried to obtain a cellulose-based thermoplastic product (CCAMB, the product is ).

[0075] The cellulose-based thermoplastic product was tested by H-NMR. The test results are as follows: Figure 7 As shown, it is explained that a cinnamate-substituted cellulose-based thermoplastic product is obtained. In addition, the thermal properties of the cinnamate-substituted cellulose-based thermoplastic product are characterized, and the DSC test results are shown in Figure 8 , indicating that the glass transition temperature of the obtained cellulose-based thermoplastic product is 115°C, and it has good thermoplasticity.

[0076] (2) Preparation of AoOTFMB / PBAT melt-spun composite fibers

[0077] Preparation of CCAMB / PBAT blend (CCAMB content is 10 wt%): 2 g of dried CCAMB and 18.0 g of PBAT (in this embodiment, the heat flow temperature of PBAT is 120° C., the molecular weight is 4.8w, and the maximum pyrolysis temperature is 378° C.) are mixed in a mixer for 4 min to obtain a CCAMB / PBAT mixture, and then the CCAMB / PBAT mixture is melt-mixed in an internal mixer at 120° C. for 8 min to finally obtain a CCAMB / PBAT blend with a CCAMB content of 10 wt%.

[0078] The obtained blend is melt-spun on a melt spinning device, and the specific steps are as follows:

[0079] 18 g of the obtained CCAMB / PBAT blend was melt-spun on a homemade spinning device at a spinning temperature of 130° C. and a winding speed of 50 m / min. The obtained CCAMB / PBAT melt-spun composite fiber had a diameter of 77 μm, a tensile strength of 46.8 MPa, and an elongation at break of 391%.

[0080] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a polysaccharide-based thermoplastic composite fiber, characterized in that: The steps include: S1. Using a homogeneous method, dissolving a polysaccharide in a polysaccharide solvent, adding a reaction reagent A to achieve a molecular-level reaction, and obtaining a polysaccharide-based thermoplastic material; S2. The polysaccharide-based thermoplastic material and the bio-based plastic are melt-blended and then added into a melt-spinning device for melt spinning to obtain a polysaccharide-based thermoplastic composite fiber.

2. The method for preparing the polysaccharide-based thermoplastic composite fiber according to claim 1, characterized in that: The S1 comprises the following steps: dissolving a polysaccharide in a polysaccharide solvent to form a polysaccharide solution, adding a reaction reagent A for reaction, wherein the reaction reagent A contains a bulky benzene ring group, and the bulky benzene ring group is used to replace the hydroxyl group on the polysaccharide to obtain a polysaccharide-based thermoplastic material with high thermal mobility. Preferably, the polysaccharide is selected from one or more of chitosan, starch, cellulose, xylan or pentosan, preferably at least one of starch, cellulose and xylan.

3. The method for preparing the polysaccharide-based thermoplastic composite fiber according to claim 2, characterized in that: The polysaccharide solvent is an ionic liquid, and the ionic liquid is selected from one or more of 1-ethyl-3-methylimidazolium chloride ionic liquid, 1-ethyl-3-methylimidazolium bromide ionic liquid, 1-allyl-3-methylimidazolium chloride ionic liquid, 1-allyl-3-methylimidazolium bromide ionic liquid, 1-butyl-3-methylimidazolium chloride ionic liquid, 1-butyl-3-methylimidazolium bromide ionic liquid, 1-ethyl-3-methylimidazolium acetate ionic liquid, 1-allyl-3-methylimidazolium acetate ionic liquid, 1-butyl-3-methylimidazolium acetate ionic liquid, 1-ethyl-3-methylimidazolium diethyl phosphate ionic liquid, N-methylpicolinate ionic liquid, 1-ethyl-3-methylimidazolium formate ionic liquid and 1-butyl-3-methylimidazolium formate ionic liquid. Preferably, the concentration of polysaccharide in the polysaccharide solution is 1-10 wt %.

4. The method for preparing the polysaccharide-based thermoplastic composite fiber according to claim 1, characterized in that: The reaction reagent A is selected from at least one of cinnamoyl chloride, 3-phenylpropanoyl chloride, 3-phenylpropionic acid, cinnamic acid, 2-trifluoromethylbenzoyl chloride, 2-trifluoromethylbenzoic acid, 2-methylbenzoyl chloride, 2-methylbenzoic acid, 2-oxytrifluoromethylbenzoyl chloride, phenylacetyl chloride, phenylacetic acid, 2-phenylpropanoyl chloride, 2-phenylpropionic acid, 2-phenylbutyryl chloride, and 2-phenylbutyric acid. Preferably, the reaction temperature of the polysaccharide solution and the reaction reagent A is 40-60° C., and the reaction time of the polysaccharide solution and the reaction reagent A is 0.5-3 h.

5. The method for preparing a polysaccharide-based thermoplastic composite fiber according to any one of claims 1 to 5, characterized in that: The bio-based plastic is selected from one or more of PLA, PCL, PHA, PBS and PBAT.

6. The method for preparing the polysaccharide-based thermoplastic composite fiber according to claim 5, characterized in that: When the bio-based plastic is PBAT, it forms a polysaccharide / PBAT composite material composition with a polysaccharide-based thermoplastic material, in which the mass fraction of PBAT is 5-95wt%.

7. The method for preparing the polysaccharide-based thermoplastic composite fiber according to claim 5 or 6, characterized in that: The melting comprises the following steps: the temperature of melting and blending the polysaccharide-based thermoplastic material and the bio-based plastic in step S2 is 80-120°C. Preferably, the melt blending of the polysaccharide-based thermoplastic material and the bio-based plastic in step S2 comprises the following steps: firstly drying the polysaccharide-based thermoplastic material and the bio-based plastic, mixing them evenly, and then melt mixing the mixture to obtain a polysaccharide-based thermoplastic material / bio-based plastic blend. According to an embodiment of the present invention, the melt spinning in step S2 includes the following steps: adding the melt-blended polysaccharide-based thermoplastic material / bio-based plastic into a preheated barrel, and performing melt spinning after preheating for 3-5 minutes, the melt spinning temperature is 110-140°C, the melt spinning drawing speed is 10-100m / min, and the diameter of the melt-spun composite fiber is 50-100μm.

8. The method for preparing a polysaccharide-based thermoplastic composite fiber according to any one of claims 1 to 4, characterized in that: In the polysaccharide-based thermoplastic material prepared in step S1, the polysaccharide-based thermoplastic material has a polysaccharide main chain, and the hydroxyl groups on the polysaccharide main chain are partially or completely replaced by bulky benzene ring groups.

9. The method for preparing a polysaccharide-based thermoplastic composite fiber according to any one of claims 1 to 4, characterized in that: The glass transition temperature of the polysaccharide-based thermoplastic material is ≤100°C; and the thermal flow temperature of the polysaccharide-based thermoplastic material is ≤120°C.

10. A polysaccharide-based thermoplastic composite fiber prepared by the method according to any one of claims 1 to 9, characterized in that: The tensile strength of the composite fiber is 40-65 MPa, and the elongation at break is 20-400%.

Citation Information

Patent Citations

  • Modified cellulose-filled PBAT / PLA composition suitable for preparing film as well as preparation and application of modified cellulose-filled PBAT / PLA composition

    CN112552655A

  • Starch / cellulose / PBAT composite film and preparation method thereof

    CN113248798A

  • Cellulose nanofibril-PBAT composite film as well as preparation method and application thereof

    CN113337013A

  • Thermoplastic cellulose / PBAT composite film and preparation method thereof

    CN114854180A